2021
DOI: 10.1029/2020wr028837
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Representation of Long‐Term Storage Variations With Conceptual Hydrological Models in Data‐Scarce Regions

Abstract: Long-term and thus low-frequency total water storage variations have been observed in many regions world-wide (Long et al., 2017;Scanlon et al., 2018). This includes long-term increasing or decreasing storage trends and multi-annual variabilities over ≥10 years. For example, decreasing storage trends were observed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 125 publications
(223 reference statements)
0
5
0
Order By: Relevance
“…Here, we have defined three HRUs that represent wetlands, hillslopes and plateaus, respectively and which are connected through a common groundwater storage (e.g. Hulsman et al, 2021). The HRUs were delineated using the MERIT hydro dataset at 60 m…”
Section: Hydrological Modelmentioning
confidence: 99%
“…Here, we have defined three HRUs that represent wetlands, hillslopes and plateaus, respectively and which are connected through a common groundwater storage (e.g. Hulsman et al, 2021). The HRUs were delineated using the MERIT hydro dataset at 60 m…”
Section: Hydrological Modelmentioning
confidence: 99%
“…Consistent inaccuracies of the bucket models in replicating slow hydrological behaviors suggest a lack of key mechanisms involved in the hydrological system. Alongside structural deficiencies (Fowler et al, 2020;Bouaziz et al, 2021), reasons for erratic model performance also involve data errors (Kuczera et al, 2010;Hulsman et al, 2021), model structural deficiencies (Fowler et al, 2020;Bouaziz et al, 2021), poor parameterization (Fowler et al, 2016(Fowler et al, , 2018, or their combination. However, model structural deficiency likely plays the key role in most cases of poor performance (Fowler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, groundwater usually responds slowly to rainfall variability and the lag time scales are mediated by the hydrogeology of aquifers and the soil physical characteristics (Hughes et al, 2012;Markovich et al, 2016). Thus, it is suggested that inter-basin groundwater flow should be incorporated in hydrological models through a new deeper groundwater reservoir to allow models to better reproduce the long-term storage fluctuations (Bouaziz et al, 2018;Hulsman et al, 2021). Although some aspects are improved by the model reconfigurations or modifications, other aspects of the hydrology behavior are still not captured or reflected well, for instance those related to the effect of the terrestrial vegetation on the long-term and slow dynamics in hydrological models (Fowler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2017) investigated the time of propagation from meteorological drought to hydrological drought, represented by SPI and SSI, respectively, and found that the propagation was a seasonal process; that is, the seasonality was effective on the propagation. Hulsman, Hrachowitz, et al (2021), Hulsman, Savenije, et al (2021) analysed spatially averaged and local drought duration, intensity and severity using precipitation, total water storage and reservoir water level data in different drought years from a basin in the Zambezi River at the border of Zambia and Zimbabwe, and found that alternative data sources improved runoff predictions in poorly gauged basins and lead to enhanced understanding of hydrological processes under dry conditions. Um et al (2022) used standardized precipitation‐evaporation index (SPEI), standardized runoff index (SRI) and standardized soil moisture index (SSMI) for meteorological, hydrological and agricultural droughts, respectively, in the Yangtze River basin, China, and found that the 12‐month indices are clearer indicators of drought propagation than the 6‐month indices as they are based on longer accumulation periods of precipitation deficit, and they become more prone to propagate into deficit in streamflow or soil moisture as their time scale increases.…”
Section: Introductionmentioning
confidence: 99%